Building an ASP.NET Intranet - Ardestani, Kourosh (Apress, 2012)
Do you want to know how you can use ASP.NET to build a modular Intranet? An intranet that could be used to share information within a small or medium sized organization? Well, congratulations, you've come to the right place!